2013
DOI: 10.1159/000346441
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-21 Induces Biological and Behavioral Alterations in Diffuse Large B-Cell Lymphoma

Abstract: MicroRNA-21 (miR-21) has been ascribed a key role in many cellular processes, e.g. tumorigenesis via inhibition of target gene expression. However, its role in diffuse large B-cell lymphoma (DLBCL) is still unclear, and there are no in-depth studies on the relationship between miR-21 and the cellular phenotype of DLBCL. In this study, we investigated the expression and role of miR-21 in the regulation of cell biological processes in DLBCL. Firstly, miR-21 expression was evaluated in three DLBCL cell lines by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
2
19
1
Order By: Relevance
“…miR-21 is believed to be a multi-functional miRNA involved in the proliferation, differentiation and anti-apoptosis of cancer cells (35). A previous study has reported that miR-21 was able to increase cell growth and inhibit apoptosis in DLBCL (36). Our findings revealed that upregulation of miR-21 not only exacerbated cell proliferation, but also suppressed the apoptosis of DLBCL cells.…”
Section: Discussionsupporting
confidence: 57%
“…miR-21 is believed to be a multi-functional miRNA involved in the proliferation, differentiation and anti-apoptosis of cancer cells (35). A previous study has reported that miR-21 was able to increase cell growth and inhibit apoptosis in DLBCL (36). Our findings revealed that upregulation of miR-21 not only exacerbated cell proliferation, but also suppressed the apoptosis of DLBCL cells.…”
Section: Discussionsupporting
confidence: 57%
“…Aberrant expression of miR-21 has been observed in various types of malignancies, and it serves an important role in tumorigenesis and other oncogenic processes by controlling the expression of target genes (8)(9)(10)(11). The current study demonstrated that miR-21 expression in Jurkat cells was significantly upregulated compared with normal lymphocytes, indicating that miR-21 may be a novel diagnostic marker for T-ALL.…”
Section: Discussionsupporting
confidence: 49%
“…It has been demonstrated that specific miRNAs act as oncogenes or anti-oncogenes by regulating cellular pathways (7). Furthermore, previous studies have suggested that miR-21 is an oncogenic miRNA that is significantly upregulated in tumor tissue, peripheral blood and particular body fluids (such as the cerebrospinal fluid) of patients with malignancies, including lung, hepatic and breast cancer, as well as B-cell and central nervous system lymphoma (8)(9)(10)(11). miR-21 binds to the 3'-UTR region of target genes, including programmed cell death 4 (PDCD4), phosphatase and tensin homolog (PTEN) and reversion inducing cysteine rich protein with kazal motifs (RECK), thus promoting proliferation and invasion whilst inhibiting apoptosis (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…48 Furthermore, gene expression analysis of different B-cell compartments demonstrated that GC B cells have markedly repressed PDCD4 expression. 18 Although rapid induction of NF-kB-dependent transcription and enhanced p70s6K signaling 10 on BCR activation are well characterized, much less is known about the potential involvement of MTOR and p70s6K in the regulation of translation initiation during the early phases of B-cell activation.…”
Section: Org Frommentioning
confidence: 99%